Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1037/dev0001246
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual review of identity integration across adulthood.

Abstract: Though Erikson recognized identity development as a lifelong project, most research on identity has focused on adolescents and emerging adults. Less is known about how the identity formed in adolescence is maintained and adapted across the adult life span. The purpose of the present paper is to provide a conceptual review and elaboration of Erikson's (1968) theory focused on identity integration, a construct that is particularly relevant to adult identity development. Identity integration describes the process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 97 publications
(160 reference statements)
2
6
0
1
Order By: Relevance
“…LGBTQ+ communities (Mitchell et al, 2021). In the same spirit as many other stories about marriage equality in our study, the narrator reported learning the following lesson from this storytelling experience: "There are so many people who fought for marriage equality for so long and it was an extremely uphill and emotional battle.…”
Section: The Stories Tell the Storysupporting
confidence: 59%
“…LGBTQ+ communities (Mitchell et al, 2021). In the same spirit as many other stories about marriage equality in our study, the narrator reported learning the following lesson from this storytelling experience: "There are so many people who fought for marriage equality for so long and it was an extremely uphill and emotional battle.…”
Section: The Stories Tell the Storysupporting
confidence: 59%
“…The theme of gaining insight is also in line with previous longitudinal research which has shown that when people repeat a narrative after several years, the focus is more on understanding and making sense of the repeated event (Negele & Habermas, 2010). Such meaning making has been found to be associated with ego-development (Bauer et al, 2005), and perceived growth (McLean et al, 2020), supporting the idea that insights gained in one specific context (such as occupation) can also be connected to identity development in other contexts as well as identity development in general (Mitchell et al, 2021;.…”
Section: The Meaning Of Change In Repeated Narratives For Identity De...supporting
confidence: 88%
“…Our results suggest that this impact can still occur in those diagnosed much later but that such challenges posed by diagnosis can be processed. Mitchell et al (2021) suggest that adult identity integration or development has two core stages, maintenance and reestablishment. Reestablishment process attempt to manage disruptions or challenges to established identity.…”
Section: Resultsmentioning
confidence: 99%